2020
DOI: 10.1101/2020.10.20.346684
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ribosome exit tunnel electrostatics

Abstract: The impact of the ribosome exit tunnel electrostatics on the protein elongation rate or on the forces acting upon the nascent polypeptide chain are currently not fully elucidated. In the past, researchers have measured the electrostatic potential inside the ribosome polypeptide exit tunnel at a limited number of spatial points, at least in prokaryotes. Here, we present a basic electrostatic model of the exit tunnel of the ribosome, providing a quantitative physical description of the tunnel interaction with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Hence, the bare surface charge density σ * is estimated to be on the surface of the spheroid cavity around the PTC. This numerical result for the surface charge density is approximately three times higher than the surface charge density prevailing on the inner surface of the ribosome exit tunnel [15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the bare surface charge density σ * is estimated to be on the surface of the spheroid cavity around the PTC. This numerical result for the surface charge density is approximately three times higher than the surface charge density prevailing on the inner surface of the ribosome exit tunnel [15].…”
Section: Resultsmentioning
confidence: 99%
“…It was hypothesized in this study that a coarse grained permittivity should be taken in the range corresponding to a mixture of protein and water, i.e at least between = 8 and r = 78. The charges which are at a distance larger than 12 from the outer surface of the cavity are so strongly screened by the dielectric medium that they can be neglected as was detailed in [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the distribution of charged residues in the ribosome exit tunnel ( 116 ) influences the landscape of cotranslational folding. For example, the positive charge density of r-proteins in E. coli is hypothesized to play a role in the cotranslational assembly of ribosomes by delaying the release of nascent r-proteins ( 117 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to determine whether such an effect can be observed in single-molecule experiments in vitro as well. Other attempts to build simplified folding machines to model aspects of co-translational peptide folding in vivo include the molecular-dynamics studies of folding in a tubular chamber representing the ribosome exit tunnel, either with uncharged elastic walls or with charged walls [ 183 , 184 , 185 , 186 ]. Finally, sophisticated methods of visualization and analysis of the massive dynamic data on protein folding, unfolding, and refolding are also undergoing active development (see [ 187 ] for a recent review).…”
Section: Review Of Protein Foldingmentioning
confidence: 99%